Caractériser les prérequis d’une université à partir de l’analyse de Parcoursup - Muriel Henry; Cathy Perret; Loris Roy (Éducation et Socialisation)
This article examines the prerequisites needed for university admission in France, that implementation of Parcoursup has revealed. Now, when applicants express their wishes for training courses, academic teams use data such as academic results, recommendations from previous institutions, or motivated training projects, to rank applications. The study focuses on the prerequisites defined by the academic teams for bachelor's degrees, based on information from a French university in 2020. The prerequisites are analyzed through three stages: the public report from Parcoursup is used for the first stage, the configuration carried out by each program in the decision-support tool used to rank candidates is examined in the second stage, and an attempt to compare the two sources of information on the prerequisites set by the academic teams for bachelor's degrees is made in the third stage. While grades play a significant role, the factors are various, ranging from academic skills to activities and interests, as well as civic commitment. Depending on the program, the criteria vary, from narrowly defined prerequisites to broader ones.